Hérétique ou dément ? Autour du procès de Thomas d’Apulie à Paris en 1388 - Maud Ternon (Criminocorpus, 2016)
In october 1388, in Paris, a trial for heresy results for the first time in the use of forensic evidence. A group of physicians find the heretic mad, which allows him to escape death penalty. During the Middle Ages, madness (insania) is used by Church in order to defame dissidents and reduce their influence on the faithful. In the beginning of the 13th century, another use of the argument of madness develops, based on the distinction between mere heretical delusion and real heresy. The naturalistic medical causality used to characterize mental illness receives in that distinction a growing place. However, forensic evidence remains absent from judicial documentation until the end of the 14th century when it becomes possible, probably thanks to the conjunction of some factors such as the ousting of the inquisitor and the propitious intellectuel climate among the masters of the University.